Characterization of polyphenols in Australian sweet lupin (Lupinus angustifolius) seed coat by HPLC-DAD-ESI-MS/MS. (February 2019) - Zhong, Liezhou; Wu, Gangcheng; Fang, Zhongxiang; Wahlqvist, Mark L.; Hodgson, Jonathan M.; Clarke, Michael W.; Junaldi, Edwin; Johnson, Stuart K.
Abstract: Seeds of the legume lupin ( Lupinus spp.) are becoming increasingly important as human food. The seed coat, at 25% of the whole seed of Lupinus angustifolius (Australian sweet lupin, ASL), is the main by-product of lupin kernel flour production. The primary market for lupin seed coat is low value feed with very limited use in foods. In this study, seed coats of six ASL commercial varieties from two growing sites were sampled for identification and quantification of polyphenols using a high-performance liquid chromatography (HPLC) with diode array detector (DAD) and coupled with a triple quadrupole mass spectrometer which equipped with electrospray ionization source (ESI-MS/MS). Three flavones (apigenin-7- O -β-apiofuranosyl-6, 8-di- C -β-glucopyranoside, vicenin 2, and apigenin-7- O -β-glucopyranoside), one isoflavone (genistein) and one dihydroflavonol derivative (aromadendrin-6- C -β-d -glucopyranosyl-7- O -[β-D-apiofuranosyl-(1 → 2)]- O -β-D-glucopyranoside), and several hydroxybenzoic and hydroxycinnamic acid derivatives were identified. Considerable variations in levels of individual polyphenols were found but apigenin-7- O -β-apiofuranosyl-6, 8-di- C -β-glucopyranoside was the predominant polyphenol in all samples accounting for 73.08–82.89% of the total free polyphenols. These results suggest that ASL seed coat could be valuable dietary source of polyphenols. Graphical abstract: Unlabelled Image Highlights: Polyphenols in Australian sweet lupin (ASL) seed coat were characterized using HPLC-ESI-MS/MS. One apigenin derivative accounted up to 83% of the total free polyphenols. Genotypic and environmental factors significantly affected both free and bound polyphenols.